Penggunaan Konsep Substitusi Formula Enteral dalam Asuhan Gizi Terstandar Untuk Pasien Efusi Perikardial, Efusi Pleura, Lipid Storage Disorder disertai Hipertensi dan Anemia: Studi Kasus Di Ruang Rawat Inap CVCU, RS X - rahmi dzulhijjah; Mohd Sarli (JOURNAL OF MEDICAL AND HEALTH SCIENCE, 2023)
Enteral formula helps meet the nutritional needs of patients who cannot eat normally, maintains bowel function, and prevents malnutrition. Formula substitution can provide greater flexibility and nutritional options to meet patient needs.This study aims to analyze the management of standardized nutritional care in patients with pericardial effusion, pleural effusion, lipid storage disorder accompanied by hypertension and anemia using enteral formula substitution. This descriptive study was conducted at X Hospital, on CVCU inpatients. Nutritional assessment was conducted by collecting anthropometric, biochemical, physical, dietary history, and personal history data. The patient was 64 years old with normal nutritional status based on estimated BMI. The patient was given liquid food with commercial formula and hospital formula via nasogastric tube (NGT) as a bolus. The results showed that the use of enteral formula substitution can meet the patient's energy, protein, fat, and carbohydrate needs during hospitalization. There was an increase in intake within 3 days of intervention, reaching >80% of the needs. The patient's body weight and nutritional status did not decrease or change. This study shows that the use of enteral formula substitution can be an effective option in standardized nutritional care in patients with complex medical conditions. Thus, enteral formula can help meet the nutritional needs of patients who cannot eat normally and prevent malnutrition.